Pediatric tinnitus: The role of neuroimaging. Issue 3 (20th March 2022) - Salman, Rida; Chong, Insun; Amans, Matthew; Hui, Ferdinand; Desai, Nilesh; Huisman, Thierry A. G. M.; Tran, Brandon
Abstract: Tinnitus is defined as the perception of sound without an external source and can be categorized as either pulsatile or nonpulsatile (ie, continuous). A variety of etiologies have been reported to cause pediatric tinnitus, many with long‐lasting implications due to hearing and concentration impairments. Therefore, imaging can be an essential part of the accurate and timely diagnosis of treatable etiologies. We describe neuroimaging findings in different etiologies of pediatric tinnitus. Etiologies of pulsatile tinnitus are frequently vascular in nature and include vascular loops, congenital vascular anomalies or variants, high riding jugular bulbs with or without a jugular bulb diverticulum, idiopathic intracranial hypertension, aneurysms, internal auditory canal hemangiomas, and petrous apex cephaloceles. Etiologies of continuous tinnitus frequently affect the middle/inner ear structures and include vestibular schwannomas, cholesteatomas, trauma, Chiari malformations, and labyrinthitis ossificans. CT and MR are often complementary modalities: CT is better suited to evaluate the integrity of the temporal osseous structures and MR is better suited to evaluate the vestibulocochlear nerve and to assess for the presence of any masses or malformations. Prompt diagnosis of the etiology of tinnitus in pediatric patients is important to avoid any potential long‐term developmental impairments. In the approach to pediatric tinnitus, categorizing the symptoms as either pulsatile versus nonpulsatile and then being aware of the possible causes and imaging findings of either can assist both the clinician and the radiologist in making an expeditious diagnosis.